Financial sustainability research: A bibliometric analysis of global scholarly output - Munandar, Muhammad Rifqi Arif; Honggowati, Setianingtyas; Sukma, Farah Ordina Ardha (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
This research employs bibliometric methods, utilizing data from the Scopus database, as well as the Bibliometrix R-package (Biblioshiny) and VOSviewer analysis tools. The analysis showed that research on Financial Sustainability experienced significant growth with an annual growth rate of 8.84% from 1987 to 2025. The literature reviewed is relatively young and influential, with an average age of 5.92 years and 13.65 citations per document. The high diversity of keywords and international collaboration (21.86%) reflects the cross-national and interdisciplinary approach. The variety of document types also enriches understanding. Publication peaks occurred in 2023 and 2024, as the urgency of sustainability issues increased globally. The United States, Italy, and the United Kingdom are the main contributors, followed by a significant increase from Asian countries. The Journal of Cleaner Production is the main reference source. Key themes such as microfinance and social inclusion show that there is still room for further exploration in this field.